2019
DOI: 10.1186/s41232-019-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of tissue-resident endothelial stem cells and their use in regenerative medicine

Abstract: Background During sprouting angiogenesis, stalk cells, localized behind tip cells, generate endothelial cells (ECs) for the elongation of new vessels. We hypothesized that stalk cells may have endothelial progenitor cell properties because of their highly proliferative ability. We conducted Hoechst dye DNA staining in ECs of preexisting blood vessels from hind limb muscle and found that endothelial-side population (E-SP) cells, which efflux Hoechst rapidly with abundant ABC transporters, show high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Recent perception of adipose tissue as merely a passive source of energy and insulation has been challenged and revised. Adipose tissue is now defined as an endocrine organ with extensive networks of auto-paracrine signalling pathways [ 6 , 7 ], as well as a rich variety of cell types, including ASCs and EPCs [ 26 , 27 ]. The reservoir of multipotent adult mesenchymal stem cells found in adipose tissue (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Recent perception of adipose tissue as merely a passive source of energy and insulation has been challenged and revised. Adipose tissue is now defined as an endocrine organ with extensive networks of auto-paracrine signalling pathways [ 6 , 7 ], as well as a rich variety of cell types, including ASCs and EPCs [ 26 , 27 ]. The reservoir of multipotent adult mesenchymal stem cells found in adipose tissue (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Adipose tissue has been found to be an abundant source of progenitor cells [ 18 , 20 ]. Pham et al suggested the existence of a distinct EPC phenotype within adipose tissue [ 17 , 19 ]. Where the stromal vascular fraction is isolated from adipose tissue and placed in culture, rapid early appearance of endothelial cells has been noted by our group and by others [ 20 , 23 , 24 , 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, great interest has developed in adipose tissue (AT) as a source of stem and progenitor cells [ 16 ], and there is substantial evidence for the stromal vascular fraction (SVF) from AT to yield cells capable of endothelial differentiation, and to promote angiogenesis in a hindlimb ischemia model [ 17 , 18 , 19 , 20 ]. These findings are supportive of the hypothesis that adipose tissue may be a source of true endothelial progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The general picture that emerges from studies performed in humans and mice indicates that CD157 expression is not restricted to the myeloid compartment but extends to tissues of different origins, such as gut [34], lung [35], eye [36], blood vascular system [37], and brain [16]. Of note, its expression frequently marks cell stemness [38][39][40].…”
Section: Cd157 Protein Structure and Tissue Distribution In Health And Diseasementioning
confidence: 99%
“…Although for a long time CD157 has remained the neglected member of the ARC family, in recent years, it has gained interest as the functional repertoire of CD157 has greatly expanded from immunity to cancer and metabolism, with a common thread of cell adhesion/migration and 'stemness' connecting all functions [16,[37][38][39][40].…”
Section: Cd157 Protein Structure and Tissue Distribution In Health And Diseasementioning
confidence: 99%